From Kant to contemporary ethics of sport - Kreft, Lev (Array, 2020)
The paper aims to establish a link between Kant’s ethics and the ethics of sport by connecting the concept of Anthropocene as the contemporary epoch during which natural history is becoming cultural history and the ethics of hope as presented in Kant’s The Critique of Judgement. The crucial moment in Kant’s argument is that choosing culture is the proper way of human progress towards civil society and cosmopolitan unity. Is sport this kind of culture? Can sport become an important moment in the contemporary ethics of hope? The answer is conditionally positive because there are obstacles present. Firstly, one of the reasons is that the modern Olympic sport was inaugurated to keep social conflicts in balance. That this purpose can be achieved suggests that the hierarchical order of excellence involved with sport competition should strengthen social hierarchies. Secondly, sport is one of the most popular and most profitable global entertainments, but it is governed by aristocratic elites with the enormous potential for the abuse of power. Thirdly, global sports organisations have a lot of political power hidden behind the Olympic mantra of the exclusion of politics from the sport.